Optimizing simulation for improvements in hard disk drive productivity - Saeheaw T. (2017)
Hard disk drive industry is an industry demand in world markets and high growth trend continued. Therefore, it is essential to develop the production line drives to high performance, be able to produce consistently and quickly. In the current process has high lead time and work in process. To improve the efficiency of production lines, this research provides a simulation using Arena OptQuest to find the best answer. The result showed 92% decrease in work in process, output was increased by an average of 31%, and waiting time was decreased 93%.